Pemanfaatan Artificial Intelligence (AI) di Era Digital untuk Gen Z pada SMKN 1 Cerme Gresik - Rony Kriswibowo; Sayyidah Hajar Faiqotul Muhimmah; Lusi Fitria Yunani; Johan Suryo Prayogo; Rusina Widha Febriana; Agung Budi Setyawan; Yeeryzkhe Githasari Lieztyanto (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
The utilization of Artificial Intelligence (AI) in the Digital Era for Gen Z at SMKN 1 Cerme Gresik aims to improve students' understanding and skills about AI technology. The study involved grade XII students and teachers, and was conducted through workshops that covered the basics of AI and its applications in daily life. The methods used included distributing questionnaires to measure students' understanding before and after the activity. Results showed significant improvement in students' understanding of AI concepts and applications, as well as higher motivation to use the technology in learning and creative projects. Despite challenges such as limited access to technology, students showed commitment to continue learning. The utilization of AI at SMKN 1 Cerme Gresik not only provides benefits in an educational context, but also prepares students to face challenges in an increasingly technology-dependent workforce.